Implementation of Supply Chain Management Information System in Non-Formal Education Business - Kisworo, Bagus; Raharjo, Tri Joko; Prasojo, Lantip Diat; Sujarwo, Sujarwo (Journal of Nonformal Education, 2022)
Information systems management is part of the implementation of educational management that must be prioritized for the advancement and development of education, so that output is in accordance with the goals made. The fact based on data from many institutions, both the government or PNF organizers, especially course and training organizers in the city of Semarang does not yet have the awareness to properly manage information systems. The aim of this study is to analyze and describe the effectiveness of the Supply Chain Management information syntem model in non-formal education businesses. This research design uses real experimental research methods (true experimental design) with pretest-posttest control group design design. This research population is participants and organizers of Course and Training Institute, Job Training Institute, Community Learning Activity Center, Course Institute, and Tutoring in Semarang city. The sampling technique used is simple random sampling numbering 260. Data collection using test instruments in the form of tiered scale coesioners. Analysis of this study data using the average difference test of two paired sample groups (Paired Sample T-Test).  Based on the results of research it is known that the implementation of supply chain management information system in noformal education business is effective as significant as a nonformal educational information system. Thus, supply chain management-based educational information systems that are often applied to business education at the higher education level are also relevant to be applied to nonformal education businesses.